The Application of Systematic Sampling Strategies for Bioarchaeological Studies in the Early Neolithic Lakeshore Site of La Draga (Banyoles, Spain). (November 2013) - Antol n, Ferran; Blanco, Àngel; Buxó, Ramon; Caruso, Laura; Jacomet, Stefanie; López, Oriol; Marlasca, Ricard; Palomo, Antoni; Piqué, Raquel; Saña, Maria; Terradas, Xavier
Abstract : This paper presents the multi-disciplinary sampling strategy that has been applied at the archaeological site of La Draga during the last three fieldwork campaigns (2010–2012). A preliminary evaluation of the results is presented in order to discuss the efficiency of the strategy in answering the outlined scientific questions. The strategies applied for faunal remains (one hundred per cent recovery), wood remains (selective sampling) and charcoal remains (random sampling of twenty-five fragments per square) proved to be successful. The anticipated levels for ichthyofauna, entomofauna and non-ligneous plant macroremains were not attained using this sampling strategy. Some explanations for this are proposed (e.g. high degree of erosion of the archaeological layer). Further guidelines for future work are established. This strategy could be applied to other Mediterranean wetland sites.